Does childhood obesity foreshadow a future time-bomb of early and more aggressive cancers? - Holly, Jeff M. P.; Samaras, Katherine (Frontiers in Endocrinology, 2026)
There has been a global explosion in the prevalence of childhood obesity with 20% of children worldwide now growing up with excess weight and, despite many calls for interventions to redress the costs to health and society, rates continue to rise. It has also recently been observed that there is a global trend with the incidence of early-onset cancers, diagnoses prior to age 50, increasing. We outline the different lines of evidence implicating that these two trends may be linked. Conclusive proof will only be obtained when longitudinal studies, initiated after the current surge in childhood obesity, mature. This will require decades, however, due to the long time-lag between exposure and cancer presentation it would then be too late to avoid a time-bomb of early cancers. This adds considerable urgency to the calls for more effective action to prevent the current epidemic of childhood obesity. The obesity epidemic is driven by an obesogenic food system to which children are particularly vulnerable. Protecting children will require broad multisector coalitions to enable sets of mutually reinforcing policies such as front-of-pack food labelling, restrictions on the ubiquitous marketing, food taxes, subsidies and mandated healthy school meal programs.